Role of T Lymphocytes in Type 2 Diabetes and Diabetes-Associated Inflammation - Chang Xia; Xiaoquan Rao; Jixin Zhong (Journal of Diabetes Research)
Although a critical role of adaptive immune system has been confirmed in driving local and systemic inflammation in type 2 diabetes and promoting insulin resistance, the underlying mechanism is not completely understood. Inflammatory regulation has been focused on innate immunity especially macrophage for a long time, while increasing evidence suggests T cells are crucial for the development of metabolic inflammation and insulin resistance since 2009. There was growing evidence supporting the critical implication of T cells in the pathogenesis of type 2 diabetes. We will discuss the available effect of T cells subsets in adaptive immune system associated with the procession of T2DM, which may unveil several potential strategies that could provide successful therapies in the future.